An Analysis of Science-Engineering Academic Library Positions in the Last Three Decades - Nestor L. Osorio (Issues in Science and Technology Librarianship)
This study analyzes the position descriptions of science engineering librarians as they are described by job advertisements. Two hundred and one positions advertised by colleges and universities during the years 1976, 1986 and 1998 were examined. The journals American Libraries, and College and Research Libraries News were the sources for collecting data. Content analysis was used to determine how the positions' qualifications and job responsibilities have changed through the years. The results show a remarkable increase in required, preferred, desired qualifications and job responsibilities for science and engineering librarians. The results also show that job announcements published in three chosen years reflect how technology has changed the role of sci-tech librarians in the last decades. In terms of salaries, it was found that salaries did not increase proportionally with the increasing number of qualifications and responsibilities. Tables and charts are included.